Analisis Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) di Industri Perhotelan Kota Jambi - IsPratiwi, Ismira Andyna; Naswir, Muhammad; Guspianto, Guspianto (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to identify the type and amount of B3 waste, identify B3 waste management based on Government Regulation Number 22 of 2021, as well as the SWOT strategy for B3 waste management in the Jambi City hotel industry. The research method is a mixed method. Data collection techniques were carried out by means of open interviews using questionnaires, documentation and literature studies. This research used two types of informants, namely 5 experts and 36 hotel staff, with a questionnaire as the data collection instrument. The results of this research are the type of B3 waste in hotels, namely used oil with the highest amount, namely 0.786 tonnes, and the smallest amount, namely used cloth, amounting to 0.009 tonnes. The research results also found that the hotels that produced the most B3 waste were 5-star hotels, amounting to 0.752 tons. The stages of B3 waste management implemented in the hotel industry are the reduction stage and the storage stage. In the SWOT diagram, it is in quadrant II, namely a combination of strategies between strengths and threats (ST strategy), namely central government regulations, administrative sanctions for hotels, reducing the use of B3 waste in hotels, preparing TPS for B3 waste not mixed with other waste, the government working together. with third parties for B3 waste management, inviting the public to protect the environment.